PENGARUH PENGETAHUAN AKUNTANSI DAN TEKNOLOGI INFORMASI TERHADAP PENGELOLAAN BARANG MILIK DAERAH DENGAN PENGGUNAAN SISTEM INFORMASI AKUNTANSI SEBAGAI VARIABEL INTERVENING (Studi Pada Dinas Kesehatan Kabupaten Bondowoso) - Pribadi, Akhmad Ribut; Karnadi, Karnadi; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2023)
The government has issued a Minister of Home Affairs Regulation (Permendagri) related to the administration of Regional Property, Number 64 of 2013 concerning the Implementation of Accrual-Based Government Accounting Standards in Regional Governments, that the accrual basis is an accounting basis in which economic transactions or accounting events are recognized and recorded, and presented in the financial report at the time the transaction occurs, and these regulations have begun to be implemented in the 2014 fiscal year. The lack of accounting knowledge for every Civil Servant (PNS) in Regional Apparatus Organizations (OPD) is due to the very low capability of Human Resources, especially in in the financial sector, so that it has an impact on the completion of recording Regional Property (BMD) which is included in the preparation of Regional Financial Reports (LKD). So the aim of this research is to analyze the influence of accounting knowledge and information technology on the use of accounting information systems and management of regional property at the Bondowoso District Health Service. The population in this study was property managers in the civil servant category at the Health Service office and 25 Community Health Centers in Bondowoso Regency. The population in this study consisted of 50 respondents. The sampling technique was determined by saturated sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 4.0 application, show that accounting knowledge has a significant positive effect on the accounting information system; Information technology has a significant positive effect on accounting information systems; Accounting knowledge has a significant positive effect on BMD Management; Information technology has a significant positive effect on BMD Management; Accounting information systems have a significant positive effect on BMD Management; Accounting knowledge on BMD Management through accounting information systems has a positive but not significant effect; Information technology on BMD management through accounting information systems has a significant positive effect.